PERAN VOLUNTEER KOMUNITAS SADILA (SAHABAT DIFABEL LAMPUNG) DALAM PENGEMBANGAN INKLUSI SOSIAL - Ririn Izzati Pangestuti; Mohammad Mona Adha; Edi Siswanto; Yunisca Nurmalisa; ⁠Abdul Halim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of volunteers of the SADILA community (Friends of Lampung Disabilities) in the development of social inclusion for children with disabilities.Social inclusion is an effort to create a friendly, fair, and equal environment for people with disabilities to participate fully in social life. This study uses a qualitative approach with a descriptive method. The research subjects were determined purposively, namely active, participatory, and passive volunteers of the SADILA community who are directly involved in assistance activities for children with disabilities. Data collection techniques are carried out through interviews, observations, and documentation. The data obtained was analyzed using qualitative data analysis techniques which included data reduction, data presentation, and conclusion drawn. The research findings indicate that volunteers of the SADILA community play an important role in the development of social inclusion for children with disabilities through various activities, such as learning assistance, arts and creativity programs, as well as educational and social campaign activities for the wider community. These volunteer roles contribute to building the self-confidence of children with disabilities, enhancing their social skills, and expanding their social interactions with the surrounding environment in promoting social inclusion. Based on these findings, it can be concluded that the role of volunteers in the SADILA Community contributes significantly to the development of social inclusion for children with disabilities.